A theoretical study on the role of ammonium ions in the double-layered V2O5 electrode. Issue 7 (15th February 2021) - Qu, Zilin; Zhou, Bo; Li, Bo; Song, Qi; Cao, Yong Hua; Jiang, Zhenyi
Abstract : Theoretical studies confirm that the NH4 + can migrate in double-layered V2 O5 with a lower energy barrier by forming the hydrated [NH4 · n H2 O] + ions. NH4 + can be used as a good pillar and it facilitates the diffusion of Li +, Zn 2+, Na + and Mg 2+ ions. Abstract : Double-layered V2 O5 and its analogues have received increasing attention as a proper cathode for Mg 2+, Na +, Li + ion batteries, even for ammonium ion batteries. Our theoretical research focuses on the effects of NH4 + ions on the structural stability and the ion diffusion properties of double-layered V2 O5 . The elastic constant calculations indicate the NH4 + and water contents have a dramatic influence on the stability of the electrode. When the ratio of H2 O and ammonia ions decreases to (NH4 )0.125 V2 O5 ·0.125H2 O, double-layered bronze will transform into other phases. The predicted specific capacity for the redox process from (NH4 )0.5 V2 O5 ·0.5H2 O to (NH4 )0.125 V2 O5 ·0.125H2 O is 54.6 mA h g −1, which agrees with the experimental value of 55.6 mA h g −1 . From the diffusion barrier calculations, it is found that the H2 O molecules can shield the polarization of NH4 + and lower the diffusion barrier of NH4 + ions. Furthermore, the migrations of common charge carriers in NH4 + pre-intercalated V2 O5 have also been studied, which implies that Li +, Zn 2+, Na +, Mg 2+ ions may move easily in the electrode with energy barriers lower than 525 meV. Our findings match well with the reported experimental results. A special structure of Mg6 NH4 V8 O20 with a much higher Mg ion concentration has been reported. Our findings show that the theoretical specific density of Mg batteries based on NH4 + pre-intercalated V2 O5 can be improved to 431 mA h g −1, which is 2.5 times larger than the reported values. This work highlights the effects of the ratio of NH4 + and H2 O on double-layered V2 O5 and provides insights into designing vanadium oxide based fast-diffusion multivalent ion conductors, which are suitable for battery applications.